Effect of the Ketoprofen Distribution in Cream-gels on the Formation of the Impurities - N. A. Lyapunov; I. A. Zinchenko; E. P. Bezuglaya; A. A. Lysokobilka (Разработка и регистрация лекарственных средств, 2019)
Introduction. The fixed combination of ketoprofen, methyl salicylate and levomenthol in the form of a cream-gel is rational. Ketoprofen forms salts with bases and esters with substances containing hydroxyl groups. Ketoprofen is practically insoluble in water, and the solubility of ketoprofen salts is much higher; this can lead to its different localization in the o/w emulsion and affect the profile of ketoprofen impurities resulting from esterification.Aim. The aim of the work is to study the effect of ketoprofen distribution in cream-gels on the formation of the impurities during storage.Materials and methods. Cream-gels with pH of 5,5 or 6,8 containing ketoprofen 2,5%, levomenthol 5% and methyl salicylate 10% have been studied. For their production, ketoprofen was dissolved in the mixture of levomenthol – methyl salicylate or in the mixed solvent of water – propylene glycol (PG) – diethylene glycol monoethyl ether (DGME). The impurities have been identified by liquid chromatography and the distribution of ketoprofen between the phases of the emulsion and the content of impurities in cream-gels have been determined by the same method. The rheological characteristics of cream-gels have been studied by viscosity-rotating viscometer method, and their microstructure – by optical microscopy.Results and their discussion. The formation of ketoprofen esters with PG, DGME and levomenthol in cream-gels have been studied. Differences in the localization of ketoprofen in the phases of the o/w emulsion at pH 5,5 and 6,8 have been shown. The formed impurities have been identified by the retention times of their peaks on chromatograms, by UV spectra and mass spectra. It has been established that during storage the content of ketoprofen esters with PG, DGME and levomenthol increased, but their formation rate was lower at pH=6,8 as well as at the adding of ketoprofen as a salt with trometamol into the dispersion medium of cream-gel. However, this resulted in formation of three impurities that were identified by UV spectra as decomposition products of methyl salicylate. When storing cream-gels with pH=6,8, the content of decomposition products of methyl salicylate, which were not detected at pH=5,5, increased.Conclusion. When making a cream-gel, ketoprofen is advisable to dissolve in a mixture of methyl salicylate and levomenthol and standardize the pH about 5,5. It is rational to use hydrophilic solvents without hydroxyl groups as penetration enhancers and the impurity profile could be limited to the menthol esters of the enantiomers of ketoprofen as a result.